Medieval Jewish Seals from Europe - Friedenberg, Samuel (Wayne State University Press, 2018)
Friedenberg's work provides the first comprehensive study of the use of seals by Jews from the 12th to the 16th century and their role in transforming Europe from a barter economy to a money economy. Structuring his analysis by geographic regions, Friedenberg examines the physical nature of the seals and discusses the symbols and legends they employ. He examines their relation to similar Christian seals, their legal validity and use, and their prevalence in certain areas at certain times. In all, 177 seals are catalogued. Where the impressions are appended to documents, the document is also reviewed. Whenever possible, the seals are illustrated, as are the most significant documents, along with other seals, medals, coins, letters and paintings which serve to illuminate the discussion of a seal. The result is the definitive catalog of all known Jewish seals of the period.